Vacuolar ATPase is required for ERK‐dependent wound healing in the Drosophila embryo. Issue 1 (7th March 2018) - Fraire‐Zamora, Juan J.; Simons, Matias
Abstract: Epithelia have the ability to repair injuries through an evolutionary conserved wound healing mechanism. Wound healing events can be classified into the transcription‐independent signals involving mobilization of ionic currents and cytoskeletal rearrangements or the transcription‐dependent response with activation of repair genes. The vacuolar H + ‐ATPase (V‐ATPase) has been implicated in the regeneration of vertebrate structures, but the underlying cellular mechanisms remain unclear. Here, we use wounding assays on the epidermis of Drosophila embryos to assess the role of the V‐ATPase in the healing response. We show that a deficient V‐ATPase induces a defective wound healing response by delaying re‐epithelialization and preventing the ERK‐dependent transcriptional activation of repair around the wound site. Our data suggests that the V‐ATPase plays an evolutionary conserved role in the activation of genes necessary for the wound healing response.